Congenital absence of small bowel with anorectal malformation - Irene Isabel P. Lim, MD, MPH; Beth A. Rymeski, DO (Elsevier, 2020)
We report a unique case of congenital absence of small bowel with associated anorectal malformation and duodenal atresia. Currently, there is no report of a similar case in a live infant in the literature. On initial exploration, the patient was thought to have colonic atresia with an anorectal malformation, and an ostomy proximal to the atretic segment was created. However, postoperative imaging revealed that the stoma was a duodenostomy. The patient subsequently underwent duodenostomy takedown and colostomy creation. He has been doing well and will undergo posterior sagittal anorectoplasty in the future.